Praktik Government Public Relations Paska Otonomi Daerah, Sebuah Tinjauan dengan Kasus Penyuluh KB Sebagai Government Public Relations Bidang KB - Aizirman Djusan (Jurnal Studi Komunikasi dan Media, 2012)
Multidimentional crisis that occurred in the late 1990s in Indonesia, has influenced the government management.  In  the  national  level,  it  appeared  a  legal  freedom  of  the  press,  and  changes  on government  Public  Relations  institution.  While  in  the  level  of  local  government,  it  was  applied  a regional  autonomy  through  the  Law  No.22/1999.  These changes  also  affected  other  sectors  of management, including Public Relations, which in government practice is called Government Public Relations.  It  beared  paradigm  shifting  in  the  field of  Public  Relations  after  1999,  as  well  as  the challenges on Government Public Relations practice due to the implementation of decentralization. Krisis  multidimensional  yang  terjadi  akhir  tahun  1990-an  di  Indonesia,  telah   mempengaruhi manajemen  pemerintahan  Indonesia.  Pada  skala  nasional,  terjadi  legalitas  kebebasan  pers  dan berpendapat,  serta  perubahan  institusi  Public  Relations pemerintahan.  Sementara  pada  level pemerintahan  daerah,  diberlakukan  penyelenggaraan  otonomi  daerah  melalui  Undang-Undang No.22/1999.  Perubahan-perubahan  tersebut  ikut  mempengaruhi  sektor  penyelenggaraan  lainnya, termasuk  bidang  Public  Relations,  yang  dalam  pemerintahan  disebut  Government  Public  Relations(Humas Pemerintah). Terjadi pergeseran paradigma bidang Public Relations setelah tahun 1999, serta tantangan praktik Government Public Relationsakibat implementasi desentralisasi.